K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 10 2019

a) \(9y^2-4x^2+6x+9y\)

\(=\left(3y-2x\right)\left(3y+2x\right)+3\left(3y+2x\right)\)

\(=\left(3y+2x\right)\left(3y-2x+3\right)\)

b) \(x^3+4x^2-12x\)

\(=x\left(x^2+4x-12\right)\)

\(=x\left(x^2-2x+6x-12\right)\)

\(=x\left(x\left(x-2\right)+6\left(x-2\right)\right)\)

\(=x\left(x-2\right)\left(x+6\right)\)

14 tháng 10 2019

a)\(9y^2-4x^2+6x+9y=\left(9y^2-4x^2\right)+\left(6x+9y\right)=\left[\left(3y\right)^2-\left(2x\right)^2\right]+3\left(2x+3y\right)\)

\(=\left(3y-2x\right)\left(3y+2x\right)+3\left(3y+2x\right)=\left(3y+2x\right)\left[\left(3y-2x\right)+3\right]=\left(3y+2x\right)\left(3y-2x+3\right)\)

b)\(x^3+4x^2-12x=x^3-2x^2+6x^2-12x=\left(x^3-2x^2\right)+\left(6x^2-12x\right)\)

\(=x^2\left(x-2\right)+6x\left(x-2\right)=\left(x-2\right)\left(x^2+6x\right)=x\left(x-2\right)\left(x+6\right)\)

14 tháng 10 2021

a) = (x - 4y)(x + 1)

b) = (x - 3y)^2 - 2^2

= (x - 3y - 2)(x - 3y + 2)

c) = x^2(x + 3) - 7x(x + 3) + 9(x + 3)

= (x + 3)(x^2 - 7x + 9)

14 tháng 10 2021

a: \(x^2-4xy+x-4y\)

\(=x\left(x-4y\right)+\left(x-4y\right)\)

\(=\left(x-4y\right)\left(x+1\right)\)

b: \(x^2-6xy+9y^2-4\)

\(=\left(x-3y\right)^2-4\)

\(=\left(x-3y-2\right)\left(x-3y+2\right)\)

3 tháng 8 2021

a) \(4x^2-9y^2+6x-9y\)

\(=\left(2x-3y\right)\left(2x+3y\right)+3\left(2x-3y\right)\)

\(=\left(2x-3y\right)\left(2x+3y+3\right)\)

b) \(1-2x+2yz+x^2-y^2-z^2\)

\(=\left(x^2-2x+1\right)-\left(y^2-2yz+z^2\right)\)

\(=\left(x-1\right)^2-\left(y-z\right)^2\)

\(=\left(x-y+z-1\right)\left(x+y-z-1\right)\)

Tick hộ mình nha 😘

10 tháng 9 2023

\(a,4x^2-4x+1\\ =\left(2x\right)^2-2.2x+1^2=\left(2x-1\right)^2\\ c,x^2-6xy-25z^2+9y^2\\ =\left(x^2-2.x.3y+9y^2\right)-\left(5z\right)^2\\ =\left(x-3y\right)^2-\left(5z\right)^2\\ =\left(x-3y-5z\right)\left(x-3y+5z\right)\)

Xem lại đề ý b

a: \(=x\left(x^2+4x+4-z^2\right)\)

\(=x\left(x+2-z\right)\left(x+2+z\right)\)

9 tháng 11 2021

z còn câu b

10 tháng 9 2021

\(a,=2xy\left(\dfrac{1}{3}x-y+2\right)\\ b,=\left(2x-3y\right)\left(2x+3y\right)-\left(2x+3y\right)=\left(2x+3y\right)\left(2x-3y-1\right)\)

b: Ta có: \(4x^2-9y^2-2x-3y\)

\(=\left(2x-3y\right)\left(2x+3y\right)-\left(2x+3y\right)\)

\(=\left(2x+3y\right)\left(2x-3y-1\right)\)

1A:

a: \(x^3+2x=x\left(x^2+2\right)\)

b: \(3x-6y=3\left(x-2y\right)\)

c: \(5\left(x+3y\right)-15x\left(x+3y\right)\)

\(=5\left(x+3y\right)\left(1-3x\right)\)

d: \(3\left(x-y\right)-5x\left(y-x\right)\)

\(=3\left(x-y\right)+5x\left(x-y\right)\)

\(=\left(x-y\right)\left(5x+3\right)\)

7 tháng 10 2021

1A. a. x(x2+2) 

b. 3(x-2y)

c. 5(x+3y)(1-3x) 

d. (x-y) (3-5x)

1B. a. 2x(2x-3)

b.xy(x2-2xy+5)

c. 2x(x+1)(x+2)

d. 2x(y-1)+2y(y-1)=2(y-1)(x-y)

 

15 tháng 10 2021

c: \(x^4+x^3-4x^2+x+1\)

\(=x^4-x^3+2x^3-2x^2-2x^2+2x-x+1\)

\(=\left(x-1\right)\left(x^3+2x^2-2x-1\right)\)

\(=\left(x-1\right)\left[\left(x-1\right)\left(x^2+x+1\right)+2x\left(x-1\right)\right]\)

\(=\left(x-1\right)^2\cdot\left(x^2+3x+1\right)\)

29 tháng 10 2021

a: \(7x-14y=7\left(x-2y\right)\)

b: \(4x^2-4x+1=\left(2x-1\right)^2\)